Fazendo a diferença: As dinâmicas da conjugalidade sorodiscordante para o HIV/AIDS - Silva, Luziana Marques da Fonseca (2012)
This work object deals with the marital dynamics of the heterosexual partner HIV serodiscordants from the metropolitan area of João Pessoa (Paraíba, Brazil). Once the HIV couple intimacy is inserted in the triangulation of the sexual study areas, the health and the gender relations, we hinge the different themes and we engage in a qualitative anthropological research with in-depth interviews and direct observation to analyze the socialcultural and symbolic aspects that condition the marital and sexual practices, the risk negotiation and the social relations of the serodiscordant subjects. The empirical analysis of these issues was discussed by three interpretative axes: the first, the impact of diagnostic disclosure and the serodiscordant marital settings; the second, the gender relations and the couple risk negotiation; and the third, the changes in marital life. The three axes showed different forms of managering the serodiscordant situation, emphasizing the early identification of the value order, the rules and the practices that guided the internal dynamic of the couple, till the impacts of to changes to the relations with social networks. The analytical reflection suggests that the serodiscordant marital settings assume different facets, these being subsumed the trajectory of the pair, the common projects, the lived moment, the gender relations, and the influence of external factors to the couple.